(1132) monetary theories of interest in the sixties: a survey النظريات النقدية للفائدة في الستينيات: دراسة استقصائية - al-jarhi, mabid ali (the institute of national planning, 2018)
during the last decade,monetary theories of interest continued to develop into two main parts. one is the theory of the rate of interest. another is the theoretical and empirical controversy over the term structure of interest rate.